La ambigüedad cultural como estrategia de resistencia - Katrin Greifeld (Estudios sobre las Culturas Contemporáneas)
A proposal for the analysis and interpretation of the colonization of the Mayo and the strategy of passive resistance through the management of the ambiguity of religious meanings and practices. The ceremony of the "Pharisees" during Lent permits the author to give us a rich and exemplary analytical description of the holy day and its meaning for the Mayo identity.